The Effect of Auriculotherapy on Climacteric, Menopause and Old Age: A Systematic Review - Seyyedeh Adeleh Rahmanian; Mahin Kiani Mask; Sedigheh Abbaspour; Morvarid Irani (Mashhad University of Medical Sciences, 2022)
Background & aim: Auriculotherapy is known as a non-invasive and safe technique that can be used by health care professionals. The purpose of this review was to explore the effects of auriculotherapy in climacteric, menopause and old age.Methods: This systematic review, which was conducted based on the PRISMA guideline, included  all clinical trials and quasi-experimental studies published in English databases of Web of Science, Scopus, PubMed, Science Direct, as well as Persian databases of SID, Magiran and IranMedex,  using the main English keywords including auriculotherapy, auricular, acupressure, auricular point pressure, ear acupuncture points, menopausal OR menopause, perimenopause, climacteric and their Persian equivalents without time restriction until May 2022. The quality of studies was assessed by two independent reviewers using Jadad scale and Effective Public Health Practice Project (EPHPP) criteria.Results: Out of 145 articles, 15 studies including 11 clinical trials with score of three and above based on the Jadad scale and four quasi-experimental studies with score of 1.51-3 based on the EPHPP criteria were examined. The results of relevant articles with a sample size of 1019 revealed that auriculotherapy reduce anxiety, intensity and frequency of hot flashes and improve the level of sex hormones, sleep disorders and quality of life in menopausal women.Conclusion: Auriculotherapy could improve the problems of elderly and menopausal women and is suggested as a complementary and alternative method of hormone replacement therapy. Considering the limited number of studies in this field, it is required to do further research along with removing the limitations of previous studies.